Aiding Low Cost Inertial Navigation With Building Heading For Pedestrian Navigation - Khairi Abdulrahim; Chris Hide; Terry Moore; Chris Hill (Cambridge University Press, 2024)
The Journal of Navigation , Volume 64 , Issue 2 , April 2011 , pp. 219 - 233